Pemanfaatan Google Classroom Sebagai Sistem Pendukung Pembelajaran Daring di Desa Pekan Bilah - Mardiah Ulfa Hasibuanh; Ela Syahfitri; Rinawati Hutabarat (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
The purpose of implementing this Community Partnership Program (PKM) is to provide knowledge in utilizing Google Classroom as a support system for online learning activities in Pekan Bilah Village. The method used in this activity is the direct method, where the team directly provides training to the participants in Pekan Bilah Village, in utilizing Google Classroom as a support system for online learning activities. The results achieved from this program are 78% of the participants are able to use Google Classroom in learning activities. Keywords: Google Classroom, Learning, Online